Analisa Overhaul Aliran Beban PMT GI 150/70 kV Menggunakan ETAP pada SUTT 70 kV - Agus Siswanto; Mudofar Baehaqi; Mansur Naufal (Nucleus Journal, 2024)
The power breaker (PMT) in the transmission system functions as a load breaker both under normal circumstances and when a disturbance occurs. In July 2021 it was discovered that there was an SF6 gas leak at (PMT) bay Arjawinangun 2 at Gi Sunyaragi. Under these conditions an overhaul was carried out which in the implementation found several sources of causes of leaks such as scale and corrosion at the joints and packing conditions that were no longer flexible. Before the implementation and after the implementation of the overhoul, tests were carried out including: contact resistance testing, insulation resistance testing and after a series of tests were carried out, then an analysis of the test results was carried out and a voltage drop simulation was carried out using the Etap 12.6 software from a series of activities, 5 simulation results were obtained and concluded that the system is still within safe limits (up 5%, down 10% from the nominal voltage). As well as other tests such as isolation resistance and contact resistance are still included in the specified standard category, so it is concluded that the PMT bay Arjawinangun 2 is in good condition and safe to operate.